ANALISIS PARKIR DI PINGGIR JALAN (ON STREET PARKING) TERHADAP KINERJA RUAS JALAN DI KOTA DENPASAR: (Studi Kasus: Pada Ruas Jalan Sulawesi, Kota Denpasar) - I Putu Febi Prayoga; Made Novia Indriani; Ida Ayu Putu Sri Mahapatni (WidyaTeknik, 2026)
The growth of economic activity and population density in Denpasar City has a direct impact on the increasing need for parking space, especially in the city center area such as Jalan Sulawesi. This study aims to analyze the characteristics of roadside parking, evaluate the performance of the road section due to the presence of such parking, and understand public perceptions of the effectiveness of parking in supporting the smooth flow of activities in the area. The method used is a quantitative descriptive approach with primary data collection through parking surveys and public perception questionnaires, as well as secondary data from related agencies. The road performance analysis was conducted based on the 1997 Indonesian Road Capacity Manual (MKJI). The results show that the characteristics of parking on Jalan Sulawesi Denpasar with the highest parking volume during 16 hours of observation are motorcycles with 222 vehicles (an average of 14 vehicles/hour) and cars with 198 vehicles (an average of 12 vehicles/hour). The performance of Jalan Sulawesi Denpasar due to roadside parking has a significant impact on decreasing road performance, characterized by an increase in the degree of saturation and a decrease in vehicle speed. Public perception shows that although roadside parking is considered practical, most respondents are aware of its negative impact on traffic flow. This study recommends more structured parking management and the development of alternative parking facilities to improve traffic efficiency in the central area of ​​Denpasar.